Răspuns :
Răspuns:
3x<-2
x<-2/3
modul de 10-x =10-x
10-x>0
x-4<0
mod de x-4=4-x
10-x-(4-x)=10-x-4+x=6
mod de a
a dacă a>=0
-a dacă a<0
[tex] 3x < -2 \Rightarrow x < -\dfrac{2}{3} [/tex]
Explicitam modulele:
[tex] x < -\dfrac{2}{3} \Rightarrow -x > \dfrac{2}{3} \Rightarrow 10-x > \dfrac{2}{3} +10 \\ \Rightarrow 10-x > \dfrac{32}{3} >0 \Rightarrow |10-x| = 10-x [/tex]
Acum pentru celălalt modul:
[tex] x < -\dfrac{2}{3} \Rightarrow x < -\dfrac{2}{3} -4 \Rightarrow x-4 < \dfrac{2}{3} -4 \\ \Rightarrow x-4 < -\dfrac{10}{3} <0 \Rightarrow |x-4| = 4-x [/tex]
Bun, acum calculăm:
[tex] |10-x| - |x-4| = 10-x-(4-x) \\ = 10-x-4+x = \tt 6 [/tex]
Explicitam modulele:
[tex] x < -\dfrac{2}{3} \Rightarrow -x > \dfrac{2}{3} \Rightarrow 10-x > \dfrac{2}{3} +10 \\ \Rightarrow 10-x > \dfrac{32}{3} >0 \Rightarrow |10-x| = 10-x [/tex]
Acum pentru celălalt modul:
[tex] x < -\dfrac{2}{3} \Rightarrow x < -\dfrac{2}{3} -4 \Rightarrow x-4 < \dfrac{2}{3} -4 \\ \Rightarrow x-4 < -\dfrac{10}{3} <0 \Rightarrow |x-4| = 4-x [/tex]
Bun, acum calculăm:
[tex] |10-x| - |x-4| = 10-x-(4-x) \\ = 10-x-4+x = \tt 6 [/tex]